Budidaya Cabai Merah Sistem Tumpangsari Pada Lahan Pekarangan Di Kota Ternate - Suwarno, Kuad; Tjokrodiningrat, Suryati; Melati, Rima (Universitas Khairun, 2024)
This study investigates the synergistic interaction of chili and tomato plants in an intercropping system of the home courtyard at Ternate City. Studies were carried out from August 2023 to March 2024 at the Maliaro housing complex, implementing a completely randomized design with three replications in the intercropping treatment with a single plant control. The study results show: (a) the synergistic interaction between chili and tomato plants is significant for the variables of plant height, development of leaf area, fruit set in the maximum growth phase, as well as components of chili and tomato fruit yields as measured by fruit weight and the percentage of healthy and damaged fruit. (b) the real synergistic effect of chilies from tomato plants on each chili plant variable, and (c) the effectiveness of the intercropping system is significantly optimal for chili plant production.Keywords: Chili, Tomato, Intercropping, Interaction, Ternate City.